Pengaruh Literasi Pajak, Sanksi Pajak, dan Kualitas Pelayanan terhadap Kepatuhan Wajib Pajak UMKM di Kota Samarinda - Ferry Diyanti; Novia Fitri Anggraeni (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to examine the effect of tax literacy, tax sanctions, and service quality on the tax compliance of MSME taxpayers in Samarinda City. This type of research is quantitative using primary data and measured using a Likert scale. The determination of the sample in this study used Purposive Sampling with a sample size of 100 respondents MSME taxpayers registered at the Pratama Tax Office (KPP Pratama) in Samarinda. The data analysis method used in this research is PLS-SEM, processed using SmartPLS version 4. The results of the study indicate that tax literacy has a positive and significant effect on the tax compliance of MSME taxpayers in Samarinda City. However, tax sanctions and service quality do not have a significant effect on the tax compliance of MSME taxpayers in Samarinda City.